1985
DOI: 10.1083/jcb.100.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans are concentrated on the sinusoidal plasmalemmal domain and in intracellular organelles of hepatocytes.

Abstract: The distribution of cell surface heparan sulfate proteoglycans (HSPGs) was determined in rat liver by immunocytochemistry. A polyclonal antibody was raised against HSPGs purified from rat liver microsomes which specifically immunoprecipitated liver membrane HSPGs. It was shown to recognize both the heparin-releasable and membrane-intercalated form of membrane HSPGs and to recognize determinants on the core protein of these HSPGs. By immunocytochemistry membrane HSPGs were localized to hepatocytes. The distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 32 publications
4
32
1
Order By: Relevance
“…By contrast, in preparations incubated with an antibody raised against liver cell membrane HSPG (28) and stained by indirect immunoperoxidase, diaminobenzidine-HCl reaction product was found on the surfaces of glomerular epithelial and endothelial cells and on the basolateral membranes of tubule epithelia (14,29), but no reaction product was detected in the GBM or in other renal basement membranes.…”
Section: When [ I S]methionine-labeled Fractions Were Analyzed Bymentioning
confidence: 81%
“…By contrast, in preparations incubated with an antibody raised against liver cell membrane HSPG (28) and stained by indirect immunoperoxidase, diaminobenzidine-HCl reaction product was found on the surfaces of glomerular epithelial and endothelial cells and on the basolateral membranes of tubule epithelia (14,29), but no reaction product was detected in the GBM or in other renal basement membranes.…”
Section: When [ I S]methionine-labeled Fractions Were Analyzed Bymentioning
confidence: 81%
“…Interestingly, immunohistochemical and immunogold electron microscopy demonstrated that the plasma membrane distribution of heparan sulfate in hepatocytes was restricted to the basolateral surface. 43 Disassociation of paracellular junction complexes exposes the basolateral surfaces of internal hepatocytes. Therefore, the increased efficiency of baculovirus-mediated gene transfer following calcium depletion may be because of the unmasking of a binding motif located on the basolateral surface of internal hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4A, B). It is known that type-I1 PLA, shows high affinity for heparin (Horigome et al, 1987) and that liver cells express large quantities of heparan sulfate proteoglycan on their surfaces (Stow et al, 1985). Incubation of cells with heparin (1 mg/ml) plus TNF for 6 h, 24 h or 52 h resulted in the appearance of increased PLA, activity in the medium (Fig.…”
Section: Presence Of Type-i1 Pla and Cpla In Brl3a Cellsmentioning
confidence: 99%